2010
DOI: 10.1166/jnn.2010.1419
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Silicon Particles for Medical Applications

Abstract: Porous silicon (PS) which has different properties from the bulk material due to the quantum confinement effects is beside other physical properties (e.g., light emitting) bioactive or even bioresorbable. The aim of this paper is to optimise the experimental conditions for the fabrication of nanostructured Si particles and to find the best methods for attaching on its surface molecules of therapeutic interest. The selective porosification has been performed using (i) a dielectric/metallic masking layer micropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…14 It has been shown that the interaction between NPs and mammalian cells (internalization and subcellular localization) varied depending on both particles properties and cell type. [15][16][17][18][19][20][21][22] Therefore, NP-cell interaction must be studied on an individual basis to establish NPs bioreactivity and cytotoxicity profiles for a desired drug delivery application.…”
Section: Introductionmentioning
confidence: 99%
“…14 It has been shown that the interaction between NPs and mammalian cells (internalization and subcellular localization) varied depending on both particles properties and cell type. [15][16][17][18][19][20][21][22] Therefore, NP-cell interaction must be studied on an individual basis to establish NPs bioreactivity and cytotoxicity profiles for a desired drug delivery application.…”
Section: Introductionmentioning
confidence: 99%
“…The authors successfully obtained sensitivity of 3-10 μg/mL level with a linear relationship between SiNW FET signals and serum CRP level, which suggested the potential of such electrochemical biosensors for an early diagnosis of gastric cancer. In addition to the semiconductor SiNWs, nanostructured silicon particles have also been used in cancer diagnosis and treatment [95,96]. Detection of multiple biomarkers simultaneously with high sensitivity and selectivity under clinically relevant conditions is important for cancer diagnosis.…”
Section: Silicon Nanowires and Nanoparticlesmentioning
confidence: 99%
“…Freestanding films were lifted-off from the substrate by increasing ten times the current density to 200 mA/cm 2 . At this point, the freestanding PS layers are fractured into small microparticles by ultrasonication in ethanol for about 20 minutes [5]. The obtained silicon microparticles morphology were morphologically analyzed using field emission gun scanning electron microscopy (FEG-SEM) -Nova NanoSEM 630 -and their image is shown in figure 1.…”
Section: Preparation and Characterization Of The Pporous Silicon Micrmentioning
confidence: 99%